Scintillation neutron detector on the basis of boron-containing plastics - Ryzhikov, V.D.; Desenko, S.M.; Kopina, I.V.; Afanasiadi, L.Sh.; Chernikov, V.V.; Onyshchenko, G.M. (Вопросы атомной науки и техники, 2004)
Main parameters are presented for plastic scintillators containing boron. These scintillators were obtained by the block polymerization method of polystyrene with luminescent dopants and allyldodecaborane. Sample dimensions: diameter 25 mm, height 25 mm. Parameters studied included light output, sensitivity to neutrons and time characteristics.